Making climate smart agriculture work for women: taking stock of evidence and implications for policy and practice - Puskur, Ranjitha; Malhotra, Aayushi (CGIAR GENDER Impact Platform, 2023)
As climate change intensifies, its negative impacts on agriculture and food systems are also accelerating, particularly affecting the smallholder vulnerable farmers, the majority of whom are women in developing countries. Climate Smart Agriculture (CSA) is designed to contribute to productivity enhancement, and support adaptation and mitigation to build resilience of farmers. However, the evidence on the factors influencing adoption of CSA by women farmers, and the consequent impacts, is scarce. This session presents the key evidence on this topic emerging from a range of activities undertaken by the CGIAR GENDER Impact Platform on this topic, including a systematic review, evidence mapping and evidence generation projects, while drawing on other available literature. The session will put a spotlight on gender-responsive climate finance, mitigation, private sector engagement and data needs that can accelerate adoption of CSA by women to build their resilience. It also highlights the key evidence and learning gaps that emerged from a learning agenda that was co-created by multiple stakeholders. Building on this information, a panel of experts from NARS, CGIAR, government, donors, development practitioners and the private sector deliberate on the policy, investment, and practice implications for their respective domains. The panel will be moderated by Puskur, Ranjitha and the panel will include: • Dr Arabinda Padhee, PS, DAFE, Odisha, India • Dr Himanshu Pathak, ICAR • Dr Alka Singh, IARI • Mr Karl Deering, CARE International • Ms Elizabeth Hernandez, Corteva • Dr Aditi Mukherjee, CGIAR • Ms Vicki Wilde, BMGF